Inspiring or confusing – a study of Finnish 1–6 teachers’ relation to teaching programming - Pörn, Ray; Hemmi, Kirsti; Kallio-Kujala, Paula (LUMAT, 2021)
There is limited research on teaching and learning of programming in primary school and even less about aspects concerning teaching programming from teachers’ viewpoint. In this study, we explore how Finnish 1-6 primary school teachers (N=91), teaching at schools with Swedish as the language of instruction, relate to programming and teaching of programming, one year after the introduction of the new national curriculum that included programming. The teachers’ relation to programming is studied by analyzing their view on programming, perceived preparedness to teach programming and their attitudes towards teaching programming. The main results of the present study are that the responding teachers approach programming in school with mixed emotions, but the majority claim to have sufficient preparedness to teach programming, and many of them have a positive attitude towards the subject. The findings indicate that the most important factor for high perceived preparedness and positive attitude is sufficient domain knowledge. The teachers’ views on programming are very diverse, ranging from focusing only on the connection to elementary step-by-step thinking to more sophisticated reasoning connecting to central aspects of computational thinking and other educational outcomes. The findings suggest that there is a need for educational efforts to make the connection between mathematical content and programming more visible for primary school teachers.